Can young agripreneurs improve their skills through agripreneurship empowerment programmes? Evidence from Africa - Adeyanju, D.F.; Mburu, J.; Gituro, W.; Chumo, C.; Mignouna, Djana B.; Mulinganya, N.; Ashagidigbi, W.M. (Elsevier, 2023)
This article examined the driving forces behind young agripreneurs’ participation in agripreneurship empowerment programmes and estimates the causal impact of programme participation on agripreneurship skills using data from a random cross-section sample of 1435 young agripreneurs in Kenya, Nigeria, and Uganda. Specifically, the study took evidence from the youth component of the African Development Bank Technologies for African Agricultural Transformation (TAAT) programme, Empowering Novel Agribusiness-Led Employment (ENABLE). An endogenous switching model was used to identify factors that significantly informed participation decisions and assess the programme’s impact on youth agripreneurship skills. Age, education, agripreneurship experience, business level, current residence, and training perception significantly influenced participation. Even though both programme participants and non-participants had high agripreneurship skills scores, participants had higher scores across the three countries than non-participants. The causal impact estimation from the switching regression model also indicates that participation has a positive and significant impact on agripreneurship skills, which implies that the higher score achieved by participants could be attributed to their involvement in the ENABLE-TAAT programme. These results suggest raising awareness of youth agribusiness empowerment programmes and encouraging youth to participate more actively. Additionally, the result suggests the need to implement strategies that could change young people’s negative perception of agricultural interventions for increased participation.